Three new species of Rabigus Mulsant & Rey (Coleoptera, Staphylininae, Philonthina) from China - Fei, Xu-Dong; Zhou, Hong-Zhang (Zootaxa, 2021)
The paper reports three new species of the genus Rabigus Mulsant & Rey from China, namely, Rabigus cuspus Fei & Zhou, sp. nov. from Sichuan, Rabigus sagittus Fei & Zhou, sp. nov. from Shanxi, Rabigus triquetrus Fei & Zhou, sp. nov. from Beijing and Shanxi. For all species included we provide color plates of general morphology and detailed aedeagus structures.